Comparando la Norma Anti-elusiva General de la Ley del Impuesto a la Renta con la Doctrina de Abuso de Derecho del Civil Law (Parte I) - Prebble, Zoë (2015)
This paper compares the general anti-avoidance rule of incometax law with the Civil Law doctrine of abuse of law (Rechtsmissbrauch, abusde droit) in eight jurisdictions: Germany, Croatia, New Zealand, Australia, France, the e uropean u nion, the u nited s tates and the United Kingdom. The paper addresses the statutory and judge-made general anti-avoidance rules in these jurisdictions and deals with the core concept of avoidance an on how these eight jurisdictions either frustrate avoidance or allow it.